EFFECT OF SITAGLIPTIN ON GLYCEMIC CONTROL, BODY WEIGHT, BLOOD PRESSURE AND SERUM LIPID PROFILE IN TYPE 2 DIABETIC HYPERLIPIDEMIC PATIENTS - Hussain, Mazhar; Atif, Moazzam Ali; Tunio, Ali Gull; Ali, Barkat; Akhtar, Lubna; Serwar, Ghulam (Journal of Ayub Medical College Abbottabad, 2016)
Background: Dyslipidaemia is a global health issue in developed as well as in developing countries. People with type 2 Diabetes mellitus are more susceptible to develop dyslipidaemia and its related complications. The objective of the study was to assess the effect of sitagliptin a (DPP-4 inhibitor) oral antidiabetic drug on blood sugar, body weight, blood pressure and dyslipidaemia in type 2 diabetic patients. Methods: This 12 weeks open label observational study was conducted at outdoor of diabetic clinic of Sheikh Zayed Medical College/Hospital, Rahim Yar Khan in which newly diagnosed type 2 diabetic patients (n=78) with poor glycaemic control(HbA1c >7.2%) were selected. The patient received sitagliptin 50 mg twice daily for 12 weeks. Results: After 12 weeks treatment with sitagliptin, there was a significant reduction in the value of HbA1c from 8.184%±0.467 at baseline to 7.0200%±0.459 at 12 weeks (p<0.05). Body weight also decreased significantly from 80.21kg±7.156 at baseline to 71.74 kg±6.567 at 12 weeks (p<0.05).Systolic blood pressure decreased (SBP) decreased significantly from 138.17±6.050 mmHg at baseline to 131.22±6.311 mmHg at 12 weeks (p<0.05). Significant changes were also seen in diastolic blood pressure which decreased from 83.14±6.714 mmHg at baseline to 75.28±6.481 mmHg at 12 weeks (p<0.05). Significant reduction in the serum level of total Cholesterol (TC), triglycerides (TG) and Low density lipoprotein cholesterol (LDL-C) were detected (TC: 222.09±13.538 to 209.41±13.475 mg/dl, p<0.05; TG: 170.99±6.940 to 143.45±8.279 mg/dl, p<0.05; LDL-C 120.00±5.804 to 109.06±6.278 mg/dl, p<0.05). High density lipoprotein cholesterol (HDL-C) increased significantly from 42.99±4.836 mg/dl at baseline to 49.97±3.490 mg/dl at 12 weeks. Conclusion: Sitagliptin not only improves blood glucose control but also body weight, blood pressure and lipid profile in type 2 diabetic hyperlipidaemia patients Keywords: Sitagliptin, Diabetes Mellitus, HbA1c, Blood pressure, Lipid profile, body weight